2007
DOI: 10.1007/s10163-007-0174-0
|View full text |Cite
|
Sign up to set email alerts
|

Noncatalytic liquefaction of tar with low-temperature hydrothermal treatment

Abstract: Water at hydrothermal and supercritical conditions is considered a promising solvent for the degradation of hazardous waste into harmless compounds. Tar liquefaction experiments were conducted using a batch-type reactor at temperatures between 623 K and 673 K and at pressures between 25 and 40 MPa. A reaction mechanism for tar liquefaction is proposed. Moreover, on the basis of the experimental results, this method could become an efficient method for tar liquefaction, producing high yields of valuable chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10] Wet air oxidation at high temperatures and pressures can be operated at conditions below or above the critical point of water (T c = 374.2掳C and P c = 22.1 MPa). Water near the critical point possesses properties very different from those of ambient liquid water: the dielectric constant is much lower and the number and persistence of hydrogen bonds are both diminished.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] Wet air oxidation at high temperatures and pressures can be operated at conditions below or above the critical point of water (T c = 374.2掳C and P c = 22.1 MPa). Water near the critical point possesses properties very different from those of ambient liquid water: the dielectric constant is much lower and the number and persistence of hydrogen bonds are both diminished.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal reactions of heavy oil have been studied in SCW, showing that two major reactions occur under supercritical conditions: oxidation and hydrolysis [57][58][59]. These reactions allow tar to be decomposed successfully into useful chemical compounds in SCW [60,61]. Hu et al [62] treated oil shale using SCW showing a higher conversion and a larger oil recovery than toluene extraction process.…”
Section: History Of Scfmentioning
confidence: 99%
“…The first common advantage of using water as solvent for clean technology is the opportunity to directly utilize water-soluble compounds and renewable materials [8][9][10][11][12]. They reported that high temperature water provided the possibility of directly modifying water-soluble and renewable materials in water without the necessary protectiondeprotection sequences that are commonly associated with conventional chemistry, thus reducing the overall synthetic steps.…”
Section: Introductionmentioning
confidence: 99%